Adherence to Plasmodium vivax malaria treatment in the Brazilian Amazon Region - Pereira, Elza A (BioMed Central, 2011)
BACKGROUND: Patients' adherence to malaria treatment is an important factor in determining the therapeutic response to anti-malarial drugs. It contributes to the patient's complete recovery and prevents the emergence of parasite resistance to anti-malarial drugs. In Brazil, the low compliance with malaria treatment probably explains the large number of Plasmodium vivax malaria relapses observed in the past years. The goal of this study was to estimate the proportion of patients adhering to the P. vivax malaria treatment with chloroquine + primaquine in the dosages recommended by the Brazilian Ministry of Health. METHODS: Patients who were being treated for P. vivax malaria with chloroquine plus primaquine were eligible for the study. On the seventh day of taking primaquine, they were visited at their home and were interviewed. The patients were classified as probably adherent, if they reported having taken all the medication as prescribed, in the correct period of time and dosage, and had no medication tablets remaining; probably non-adherent, if they reported not having taken the medication, in the correct period of time and dosage, and did not show any remaining tablets; and certainly non-adherent, if they showed any remaining medication tablets. RESULTS: 242 of the 280 patients reported having correctly followed the prescribed instructions and represented a treatment adherence frequency (CI95%) of 86.4% (81.7%-90.1%). Of the 38 patients who did not follow the recommendations, 27 (9.6%) were still taking the medication on the day of the interview and, therefore, still had primaquine tablets left in the blister pack. These patients were then classified as certainly non-adherent to treatment. Although 11 patients did not show any tablets left, they reported incorrect use of the prescribed therapy regimen and were considered as probably non-adherent to treatment. CONCLUSIONS: Compliance with the P. vivax malaria treatment is a characteristic of 242/280 patients in the surveyed region. However, the group of non-adherent patients can have an impact on the magnitude of transmission and relapses of P. vivax infections currently observed in the studied area. Simple practices can be introduced in the healthcare services in order to improve compliance with the treatment prescribed.